(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency and causes of accidental upper limb amputations seeking rehabilitation (prosthesis) care in a tertiary care center Study Design: Observational Descriptive Study Place and Duration of Study: This study was carried out at outpatients Department of Institute of Physical Medicine and Rehabilitation at Dow University of Health Sciences, Karachi from Jan 2007 to Dec 2010. Materials and Methods: The Sampling Technique was non Probability Purposive sampling. A study specific Performa was prepared which included patient age, stump complications, level of amputation and associated risk factors. The data was analyzed in SPSS version 15. Results: The Mean±SD age of ULA was 28.56 ±SD 11.97 (years). Most ULA were reported from Karachi 65 (67.7%). Labourers were the most commonly affected groups 33(34.4 %).Accidents leading to ULA were reported in 89(92.70) and machine injury (chaff cutting) was responsible in one third of the ULA. Quarter of the ULA had leading cause electric injury. Only, 16 (16.7%) amputees had road traffic accidents. Conclusion: The study concluded that majority of upper limb amputation were caused by machine accidents affecting mostly labourers. Therefore, machine safety protocols for labourers, farmers and workers should be implemented in their local language and through pictoral messages and inbuilt safety measures machines should be sold by company representatives